2010
DOI: 10.1002/clc.20539
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Aspirin Resistance in Patients With Chest Pain

Abstract: BackgroundThere are conflicting data in the literature about the clinical significance of aspirin resistance.HypothesisWe aimed to prospectively evaluate the prevalence of biochemical aspirin resistance in patients on aspirin therapy who were admitted to the emergency clinic with chest pain. We also aimed to evaluate the relation between acute coronary syndromes (ACS) and aspirin resistance.MethodsA total of 338 patients were included in the study. Platelet reactivity was measured with the PFA‐100 system (Dade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Among patients admitted to the emergency room with chest pain, Aydinalp et al 55 showed nearly a 2-fold increase in the prevalence of aspirin resistance, using the PFA-100 assay, in those patients with a confirmed diagnosis of ACS compared to those who had been ruled out for ACS (40.7% vs 17.2%). Similarly, patients with acute MI (NSTEMI or STEMI) are more likely to be aspirin resistant than in those without acute infarction.…”
Section: Post-acsmentioning
confidence: 99%
“…Among patients admitted to the emergency room with chest pain, Aydinalp et al 55 showed nearly a 2-fold increase in the prevalence of aspirin resistance, using the PFA-100 assay, in those patients with a confirmed diagnosis of ACS compared to those who had been ruled out for ACS (40.7% vs 17.2%). Similarly, patients with acute MI (NSTEMI or STEMI) are more likely to be aspirin resistant than in those without acute infarction.…”
Section: Post-acsmentioning
confidence: 99%
“…High on-treatment platelet reactivity is linked to worse outcomes for both STEMI and NSTEMI patients undergoing procedures [17]. Platelet reactivity and anti-platelet resistance is suggested to be higher in STEMI patients than NSTEMI patients [18-20]. These differences in platelet reactivity and disease progression may result from gene expression differences between STEMI and NSTEMI cases.…”
Section: Introductionmentioning
confidence: 99%
“…What is inspiring is that the contribution of countries such as Turkey played a bigger role in producing articles related to aspirin resistance. Several studies conducted in Turkey reported a high frequency of aspirin resistance in patients with kidney failure [72,73], acute coronary syndrome [74][75][76], hypertension [77], chest pain [78], metabolic syndrome [79,80], diabetes mellitus [81], stroke [76], systemic lupus erythematosus [82] and cigarette smoking [83]. These results might open the door for new ideas and questions for research related to aspirin resistance.…”
Section: Discussionmentioning
confidence: 99%